2007
DOI: 10.1111/j.1748-1716.2007.01710.x
|View full text |Cite
|
Sign up to set email alerts
|

Human cardiovascular dose–response to supplemental oxygen

Abstract: There is a linear dose-response relationship between arterial oxygen and cardiovascular parameters when the systemic oxygen tension increases above normal. A direct effect of supplemental oxygen on the vessels may therefore not be excluded. Proximal aortic and peripheral resistance increases from hyperoxaemia, but a decrease of venous return implies extra cardiac blood-pooling and compensatory relaxation of the capacitance vessels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
64
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 54 publications
7
64
0
Order By: Relevance
“…Prolonged O 2 breathing causes minor hemodynamic changes, such as bradycardia, and slight decreases in stroke volume and cardiac output (55). After O 2 exposure, we observed nothing outside of the physiological range in terms of heart rate and cardiac output in HO-1(CM) -/-mice.…”
Section: Discussionmentioning
confidence: 76%
“…Prolonged O 2 breathing causes minor hemodynamic changes, such as bradycardia, and slight decreases in stroke volume and cardiac output (55). After O 2 exposure, we observed nothing outside of the physiological range in terms of heart rate and cardiac output in HO-1(CM) -/-mice.…”
Section: Discussionmentioning
confidence: 76%
“…22 It has been demonstrated that hyperoxia may influence systemic vascular resistance, stroke volume and BP. 23,24 Thus, the lack of blood-pressure decrease during chemoreflex deactivation can be explained by local vasoconstricting effect of hyperoxia that could offset the sympathoinhibitory effect of chemoreceptor deactivation. To clarify the influence of carotid body deactivation on the circulatory parameters in hypertensive patients, a more detailed hemodynamic approach including cardiac output measurement would need to be applied.…”
Section: Discussionmentioning
confidence: 99%
“…The circulatory effects of hyperoxia were described in healthy subjects and patients with heart failure. 23,24 Long periods of breathing 100% oxygen increased systemic resistance, decreased stroke volume and impaired left ventricular relaxation. It has been shown in the animal model 27 that shorter periods of hyperoxia inhibit ventilatory and circulatory chemoreflex response.…”
Section: Discussionmentioning
confidence: 99%
“…Hemodynamic changes such as decrease in heart rate, cardiac output and stroke volume were reported in hyperoxic breathing (2,12,16,24,34). The lowering of heart rate in hyperoxic condition may be triggered by increased parasympathetic activity (24).…”
Section: Discussionmentioning
confidence: 99%